Structural dynamics of ligand diffusion in the protein matrix: A study on a new myoglobin mutant Y(B10) Q(E7) R(E10) - BRUNORI, Maurizio; CUTRUZZOLA', Francesca; TRAVAGLINI ALLOCATELLI, Carlo; VALLONE, Beatrice; C. Savino; Q. H. Gibson (Biophysical Journal, 1999)
A triple mutant of sperm whale myoglobin (Mb) [Leu(B10) --> Tyr, His(E7) --> Gln, and Thr(E10) --> Arg, called Mb-YQR], investigated by stopped-flow, laser photolysis, crystallography, and molecular dynamics (MD) simulations, proved to be quite unusual. Rebinding of photodissociated NO, O-2, and CO from within the protein tin a "geminate" mode) allows us to reach general conclusions about dynamics and cavities in proteins. The 3D structure of oxy Mb-YQR shows that bound O-2 makes two H-bonds with Tyr(B10)29 and Gln(E7)64; on deoxygenation, these two residues move toward the space occupied by O-2. The bimolecular rate constant for NO binding is the same as for wild-type, but those for CO and O-2 binding are reduced 10-fold. While there is no geminate recombination with O-2 and CO2 geminate rebinding of NO displays an unusually large and very slow component, which is pretty much abolished in the presence of xenon. These results and MD simulations suggest that the ligand migrates in the protein matrix to a major "secondary site," located beneath Tyr(B10)29 and accessible via the motion of Ile(G8)107; this site is different from the "primary site" identified by others who investigated the photolyzed state of wild-type Mb by crystallography. Our hypothesis may rationalize the O-2 binding properties of Mb-YQR, and more generally to propose a mechanism of control of ligand binding and dissociation in hemeproteins based on the dynamics of side chains that may (or may not) allow access to and direct temporary sequestration of the dissociated ligand in a docking site within the protein. This interpretation suggests that very fast (picosecond) fluctuations of amino acid side chains may play a crucial role in controlling O-2 delivery to tissue at a rate compatible with physiology.